Watching Earth from Space How Surveillance Helps Us -- and Harms Us - Norris, Pat.; SpringerLink (Online service) (New York, NY : Praxis : Imprint: Praxis, 2010)
- Are satellites a threat to individual privacy? - How bad is climate change and global warming? - Why can we not find Osama bin Laden? - Does the world have enough fresh water? Watching Earth from Space gives you the answers to these and many other burning questions of the day. This is the story of how our planet is being monitored by hundreds of space-borne instruments for both military and peaceful reasons. It highlights the technical challenges of those instruments and describes the agencies that gather useful information from them. But as well as all the essential monitoring performed by satellites - such as mapping natural or man-made disasters, agricultural performances, weather, and climate change to name a few - there is a growing swell of public opinion that they are being used by governments to erode personal privacy and freedom. This book looks at the possible conflict between public good and market forces, and the future development of new systems to deal with new needs.
The threat of satellite images -- Weather satellites -- Climate change -- Commercial surveillance: mapping on a large scale -- Society and survival -- Where am I? Where are they? -- Monitoring nuclear weapons1 -- Military imaging satellites: long-range intelligence -- Military radio surveillance from space -- The future.
Keywords: Geography; Remote sensing; Life sciences; Astronautics; Earth Sciences; Remote Sensing/Photogrammetry.; Popular Science in Nature and Environment; Measurement Science and Instrumentation; Aerospace Technology and Astronautics